Clinical Characteristics and Surgical Outcomes of Turkish Patients With Pediatric Glaucoma Who Underwent Glaucoma Surgery in a University Hospital - ERASLAN, MUHSİN (My University, 2024)
Purpose: To describe the clinical characteristics and outcomes of a pediatric cohort surgically treated for primary or secondary pediatric glaucoma (PPG/SPG). Methods: A retrospective chart review was conducted of all patients with pediatric glaucoma who had surgery between 2013 and 2021. Relevant demographic and clinical data were cumulated and analyzed. Results: Forty-two eyes of 29 patients (18 girls and 11 boys) were included: 22 (52.4%) primary congenital glaucoma (PCG), 7 (16.7%) juvenile open-angle glaucoma, and 13 (30.9%) SPG. Mean ages at presentation were 2.57 ± 2.87, 131.96 ± 27.71, and 62.09 ± 65.12 months, respectively. In this study, eyes with PCG presented the earliest, with the highest intraocular pressure (IOP) and thickest central corneal thickness (CCT). The mean number of glaucoma surgeries was 1.48 ± 0.71, with 38.1% of the eyes needing two or more glaucoma surgeries; trabeculectomy was the most frequent glaucoma surgery in this cohort. After surgical intervention, the overall mean IOP dropped from 32.25 ± 12.97 to 18.10 ± 9.23 mm Hg (P < .001). Moreover, the percentage using antiglaucoma medications decreased from 100% to 35.7% at the final visit, as did the number of medications prescribed per eye (2.69 ± 0.92 vs 1.05 ± 1.46, P≤ .001). Mean best corrected visual acuity (BCVA), in patients who could have their BCVA measured, improved from 0.61 ± 0.61 to 0.53 ± 0.51 logMAR at final follow-up. Conclusions: Surgical intervention was shown to provide a well-controlled IOP, decrease dependance on glaucoma medications, and improve BCVA in both PPG and SPG. Multiple surgical interventions may be necessary in the treatment of some pediatric patients with glaucoma. Prognostically, thicker CCT was significantly associated with worse IOP control, more glaucoma surgeries, and more antiglaucoma medications at the final visit. Initial BCVA correlated significantly with BCVA at the final visit.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; GÖZ HASTALIKLARI; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; OPHTHALMOLOGY; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Oftalmoloji; Pediatrics, Perinatology and Child Health; Ophthalmology